A Combined Raman Spectroscopic and Thermogravimetric Analysis Study on Oxidation of Coal with Different Ranks - Weiqing Zhang; Shuguang Jiang; Christopher Hardacre; Peter Goodrich; Kai Wang; Hao Shao; Zhengyan Wu (Journal of Analytical Methods in Chemistry)
Raman spectroscopy and nonisothermal thermogravimetric analysis (TGA) measurements have been reported for different rank coals (lignite, bituminous coal, and anthracite) and the relationship between the measurements was examined. It was found that the Raman spectra parameters can be used to characterize structure changes in the different rank coals, such as the band area ratios based on the curve-fitted results. Higher ranked coal was found to have higher values of IGR/IAll and IG+GR/IAll but lower values of ID/I(G+GR), IDL/I(G+GR), IS+SL/I(G+GR), and I(GL+GL')/I(G+GR). The oxidation properties of the coal samples were characterized by the reactivity indexes Tig, T20%, and Tmax from TGA data which were found to correlate well with the band area ratios of IGR/IAll, IG+GR/IAll, and IS+SL/I(G+GR). Based on these correlations, the Raman band area ratios were found to correlate with the oxidation activity of coal providing additional structural information which can be used to understand the changes in the TGA measurements.